A comprehensive evaluation of the EU's biofuel policy: From biofuels to agrofuels - Kitty Murnaghan (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
During a time in which the subject of climate change is deemed high on the list of priorities of many governments, it is important to assess to what extent policies in this field are achieving meaningful results. The link between energy usage and global warming is clear and today in the European Union the use of renewable resources is being promoted more than ever before. The move towards a renewables based economy has clear benefits over a fossil fuel based one with regards to climate change and the environment, however if the implementation of renewables is not monitored and regulated then this is not a given by any means. Of the renewable resources, bioenergy has a high level of importance in the EU. For this reason, this paper will make a comprehensive evaluation of the EU's biofuel policy in order to assess what the driving forces behind the regulation of this resource are, and how they affect to what extent it is successful or not. In order to do this, firstly the impacts of current EU bioenergy consumption will be assessed, to determine whether it is achieving the stated and desired climate goals or not. Findings will show that in fact the current formulation of Europe's Renewable Strategy creates pressure to meet binding targets for renewable usage and the resultant rapid increase in the demand for bioenergy has caused a number of negative social and ecological impacts to arise. Therefore in light of this, the current systems in place at the EU level meant to regulate the use of bioenergy and ensure it is implemented in a sustainable way will be critically analysed in order to find out how such negative impacts have been able to occur. The final section will then look into the driving forces responsible for regulation of this kind through a case study of Germany and Indonesia.
Keywords: Q16; Q28; Q21; Q56; F23; K32; 330; European Union energy policy; agrofuel; biofuel; renewable energy; sustainability criteria